COMPARISON OF EFFECTIVENESS AND SAFETY OF CAFFEINE VERSUS AMINOPHYLLINE FOR APNEA OF PREMATURITY (The Research of Medical Science Review, 2024)
Introduction: Globally, it is estimated that approximately 15 million children are born prematurely each year, and sadly, around 1 million of these precious lives are lost due to complications associated with prematurity. In the field of neonatology, Methylxanthine therapies, which encompass the administration of substances such as caffeine and theophylline, have emerged as a cornerstone in the treatment and prevention of apnea of prematurity. The primary objective of this particular investigation was to ascertain and evaluate the comparative efficacy of aminophylline and caffeine citrate in the management and subsequent prevention of apnea of prematurity, specifically after the occurrence of one or two initial episodes of apnea. The overarching aim of this study was to gather sufficient evidence in order to establish effective guidelines within the context of Pakistan, thereby facilitating informed decision-making regarding the utilization of either methyxanthine substance, namely aminophylline or caffeine citrate, as the initial therapeutic intervention for infants suffering from apnea of prematurity. By undertaking such an endeavor, the hope is to enhance the overall quality of care provided to these vulnerable neonates, ultimately improving their prognosis and long-term outcomes. Methodology: The investigation was conducted at the Neonatal Intensive Care Unit (NICU) situated within the esteemed confines of SUGHRA SHAFI MEDICAL COMPLEX, NAROWAL, spanning the time period from March 13, 2023, to September 13, 2023. To procure the necessary information, diligent efforts were made to collect data from the parents of a total of 172 patients, with an equitable distribution of 86 parents in each group. In order to ensure unbiased results, the neonates were randomly assigned to one of two groups. Those neonates who were fortunate enough to be allocated to the caffeine citrate group were administered a loading dose of 20mg/kg of caffeine citrate, while their counterparts in the Aminophylline group were administered a loading dose of 5mg/kg of aminophylline. Throughout the duration of the investigation, the neonates were meticulously monitored to determine the efficacy and impact of the administered caffeine citrate or aminophylline. The ultimate outcome of the neonates, which was meticulously recorded and documented, entailed the cessation of apnea for a prolonged period of 48 hours. To ensure the validity and reliability of the data, a diligent effort was made to enter and analyze the collected data using the highly esteemed and widely used statistical software, SPSS version 25.0. Results: In Aminophylline group, 51(59.3%) were males and 35(40.7%) were females, while in Caffeine citrate group, 54(62.8%) were males and 32(37.2%) were females. The mean age of patients in Aminophylline was 20.55±5.41 hours and in Caffeine citrate was 20.78±5.38 hours. In Aminophylline group, 67(77.9%) had efficacy and 77(89.5%) in Caffeine citrate group with a p-value 0.039, which is statistically significant. Conclusion: The administration of caffeine citrate, a compound derived from caffeine, was determined to be significantly more practical and convenient in the context of medical treatment, while also effectively promoting and facilitating breastfeeding among premature infants in the Neonatal Intensive Care Unit (NICU). Moreover, it has been established that caffeine citrate serves as a highly effective alternative to aminophylline, a medication commonly used for preventing apnea of prematurity, a condition characterized by the temporary cessation of breathing in premature infants. Therefore, given its numerous benefits and advantages in terms of administration, convenience, and promotion of breastfeeding, caffeine citrate has emerged as an indispensable pharmacological intervention in the NICU setting.